Improving outcome of in vitro sperm activation using non-liquefied versus liquefied semen of oligoasthenozoospermic patients - Muhammad Fakhrildin (Tehran University of Medical Sciences, 2010)
Objective: To evaluate the efficacy of in vitro sperm activation (ISA) using non-liquefied versus liquefied asthenozoospermic semen samples for improvement of sperm parameters. Materials and Methods: Fifty six oligoasthenozoospermic (OA) patients (age range: 22-44 years; mean: 32.089 years) were enrolled in this study. OA patients were classified according to type of infertility. Also, duration of infertility was recorded. Fifty six semen samples were collected, and seminal fluid analyses were done involving macroscopic and microscopic examinations were performed according to WHO methodology. Direct swim-up technique was used to separate the motile spermatozoa from seminal plasma. Minimum Essential Medium Eagle (MEME) enriched with 5% Human serum albumin (HSA) was used. One mL of either non-liquefied or liquefied semen was layered beneath 1 mL of MEME enriched with 5% HSA, and placed for incubation in an air incubator at 37 oC for 30 minutes. Then, one drop (10 μL) from upper layer of culture medium was taken using automatic pipette to be examined under high power field (40 X) for assessment of sperm parameters. Results: According to type of infertility, infertile patients were classified into patients with either primary infertility (no. 46; 82.15 %) or secondary infertility (no. 10; 17.85 %). In contrast to other parameters, significant (P<0.05) reductions were noticed in the percentages of sperm motility and progressive sperm motility for OA patients with primary infertility as compared to OA patients with secondary infertility. All sperm parameters were significantly (P<0.001) enhanced after in vitro activation of liquefied and non-liquefied semen samples when compared to pre-activation. In the present study, best results were achieved for non-liquefied semen samples as compared to liquefied semen samples. Conclusion: It was concluded that the outcome of ISA was enhanced in regard to sperm parameters when using non-liquefied semen of OA patients. Furthermore, some components of seminal plasma of OA patients may be have harmful effects on certain sperm functions when in vitro incubated for longer periods. Further study is recommended to investigate the effect of in vitro sperm activation from non-liquefied semen on successful rate of artificial insemination husband.